Do Unions Affect Pay Methods of Canadian Firms? A Longitudinal Study - J. Long, Richard; L. Shields, John (Relations industrielles / Industrial Relations, 2009)
SummaryDrawing on two waves of survey data collected from 250 Canadian firms in 2000 and 2004, this study examines union influence on the mix of compensation methods used by employers. As expected, firms with more unionization devoted a larger proportion of total compensation to indirect pay (also known as “employee benefits”) than did firms with less unionization, a finding that held in both time periods. However, while more unionized firms devoted a smaller share of compensation to individual performance pay in 2000, this was not true in 2004. Also surprising, more unionized firms did not differ significantly from less unionized firms in their proportions of base pay, group performance pay, or organizational performance pay in either time period. The paper concludes that although unions may still have the power to influence some aspects of the wage bargain (i.e. the compensation mix), this power may be declining.